The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1111/j.1574-6968.2002.tb11379.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular viability of toxigenicCorynebacterium diphtheriaestrains in HEp-2 cells

Abstract: Corynebacterium diphtheriae, generally considered an extracellular coloniser, was evaluated for its ability to enter and survive within HEp-2 monolayers by gentamicin protection assay. Intracellular viability of HC01 strain, isolated from endocarditis, was more expressive (2.59%) than observed in 241 (0.21%) and CDC-E8392 (1.93%) strains. Electron microscopy of C. diphtheriae-infected HEp-2 cells revealed intracellular bacteria inside membrane-bound vacuoles. Bacterial internalisation was totally inhibited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Adhesion of different C. diphtheriae strains to lung, pharyngeal, and laryngeal epithelial cells and to erythrocytes has been reported (Colombo et al 2001;Bertuccini et al 2004;Hirata et al 2002Hirata et al , 2004. Although it is known that both cell-wall-linked surface proteins and fibrous protein polymers, for example fimbriae and pili, are of major importance in the adhesion process for many types of Gram-positive bacteria, many aspects of the underlying mechanisms remain unclear (Rogers et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Adhesion of different C. diphtheriae strains to lung, pharyngeal, and laryngeal epithelial cells and to erythrocytes has been reported (Colombo et al 2001;Bertuccini et al 2004;Hirata et al 2002Hirata et al , 2004. Although it is known that both cell-wall-linked surface proteins and fibrous protein polymers, for example fimbriae and pili, are of major importance in the adhesion process for many types of Gram-positive bacteria, many aspects of the underlying mechanisms remain unclear (Rogers et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Using a combination of gentamicin protection assays and thin-section electron microscopy, Hirata and co-workers [8] showed that toxigenic C. diphtheriae were not only able to adhere to laryngeal HEp-2 cells, but also enter these cells and survive after internalization. Similar observations were made for non-toxigenic strains [9] showing that also pharyngeal Detroit 562 cells can be invaded by C. diphtheriae .…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of gentamicin protection assays and thin-section electron microscopy, Hirata and co-workers [9] showed that toxigenic C. diphtheriae are not only able to adhere to laryngeal HEp-2 cells, but also enter these cells and survive after internalization. Similar observations were made for non-toxigenic strains [10] showing that also pharyngeal Detroit 562 cells can be invaded by C. diphtheriae and that viable intracellular bacteria can be detected up to 48 h after infection.…”
Section: Introductionmentioning
confidence: 99%